Penetration Evaluation of Explosively Formed Projectiles Through Air and Water Using Insensitive Munition: Simulative and Experimental Studies - Ahmed, M.; Malik, A. Q.; Rofi, S. A.; Huang, Z. X. (Engineering, Technology & Applied Science Research, 2016)
The process of formation, flying, penetration of explosively-formed projectiles (EFP) and the effect of water on performance of the charge for underwater applications is simulated by Ansysis Autodyn 2D-Hydro code. The main objective of an explosively formed projectile designed for underwater applications is to disintegrate the target at longer standoff distances. In this paper we have simulated the explosively formed projectile from OFHC-Copper liner for 1200 conical angle. The Affect of water on the penetration of EFP is determined by simulations from Ansysis Autodyn 2-D Hydrocode and by varying depth of water from 1CD-5CD. The depth of penetration against steel target is measured experimentally. Flash X-Ray Radiography (FXR) is used to capture EFP jet formation and its penetration against target is measured by depth of penetration experiments. Simulation results are compared with experimental results. The difference in simulated and experimental results for depth of penetration is about 7 mm, which lies within favorable range of error. The jet formation captured from FXR is quite clear and jet velocity determined from Flash X-ray radiography is the same as the ones obtained by using other high explosives. Therefore, it is indicated that Insensitive Munition (8701) can be utilized instead of Polymer Bonded Explosives (PBX) for air and underwater environments with great reliability and without any hazard.